1997
DOI: 10.1148/radiology.202.3.9051043
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic breast biopsy of atypical ductal hyperplasia and ductal carcinoma in situ lesions: improved accuracy with directional, vacuum-assisted biopsy.

Abstract: Directional, vacuum-assisted biopsy resulted in statistically significantly fewer cases of ADH or DCIS underestimation of disease without clinical complications or the creation of postbiopsy mammographic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
2
9

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(136 citation statements)
references
References 0 publications
7
115
2
9
Order By: Relevance
“…Recent studies have found improved accuracy with the 14-gaugevacuum-assisted biopsy device (Mammotome; Biopsys Mcdi cal [Ethicon Endo-Surgery, a Johnson & Johnson company], Irvine, CA) compared with the 14-gauge large-core biopsy device in characterizing both atypical ductal hyper plasia lesions [9â€" I 1] and ductal carcinoma in situ (DCIS) lesions [9] and in capturing calcifications (as shown on specimen radio graphs) [12†"14]. The 14-gauge vacuum-as sisted device also completely removed a higher percentage oflesions on which biopsy was performed as evaluated on images after biopsy [15†"17].…”
Section: N Eedle-localized Breast Biopsy Hasmentioning
confidence: 99%
“…Recent studies have found improved accuracy with the 14-gaugevacuum-assisted biopsy device (Mammotome; Biopsys Mcdi cal [Ethicon Endo-Surgery, a Johnson & Johnson company], Irvine, CA) compared with the 14-gauge large-core biopsy device in characterizing both atypical ductal hyper plasia lesions [9â€" I 1] and ductal carcinoma in situ (DCIS) lesions [9] and in capturing calcifications (as shown on specimen radio graphs) [12†"14]. The 14-gauge vacuum-as sisted device also completely removed a higher percentage oflesions on which biopsy was performed as evaluated on images after biopsy [15†"17].…”
Section: N Eedle-localized Breast Biopsy Hasmentioning
confidence: 99%
“…Previous studies have shown that while CNB is highly reliable and sensitive for distinguishing between malignant and benign disease [1][2][3], it is less reliable for diagnosing atypical ductal hyperplasia (ADH). For patients diagnosed with ADH at CNB, the rate of upgrade to ductal carcinoma in situ or invasive cancer at follow-up surgical excision is reported as 19-87% [4][5][6][7][8][9]. Therefore, follow-up surgical excision is generally recommended when ADH is diagnosed at CNB.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] With the increasing use of needle core biopsy as the initial diagnostic workup in dealing with breast lesions, and the widespread use of mammographic screening resulting in increased detection of asymptomatic calcifications, more and more ductal carcinomas in situ (DCISs) are being detected using needle core biopsy. However, some cases of needle core biopsy-diagnosed DCISs turned out to be invasive in the final excisions.…”
mentioning
confidence: 99%